=(3lg2+3lg10)lg5+3(lg2)^2-lg6+lg6-3lg1 =(3lg2+3lg2+3lg5)lg5+3(lg2)^2 =6lg2lg5+3(lg5)^2+3(lg2)^2 =3 ( (lg2)^2+2lg2lg5+(lg2)^2 ) =3 (lg2+lg5)^2 =3
计算(lg8+lg1000)*lg5+3(lg2)+lg6(负一次方)+lg0.006
1个回答
相关问题
-
(lg8+lg1000)lg5+3(lg2)²+lg6-¹ +lg0.006.怎样计算
-
计算:lg5(lg8+lg1000)+(lg2^√3)^2+lg1/6+lg0.06.
-
(lg16+lg10000)lg5+4(lg2)^2-lg6+lg0.006 如何计算
-
lg5 (lg8+lg1000)+(lg2 )(lg2 )+lg0.06+lg1/6
-
lg5(lg8+lg1000)+(lg2^√3)^2+lg1/6+lg0.06等于
-
lg5(lg8+lg1000)+3lg2+lg1\6+lg0.06怎样算?
-
√[﹙lg3﹚³-lg9+1﹙lg√27+lg8-lg√1000﹚]/lg0.3lg1.2
-
lg5(lg8+lg1000)+(lg2倍根3)^2+lg1/6+lg0.06要详细步骤
-
{√[(lg3)^2-lg9+1] *(lg√27+lg8-lg√1000)}/(lg0.3*lg1.2)
-
计算(lg2)3次方+(lg5)3次方+3lg2乘以lg5